Defining Distinctiveness Aspect of Place Identity in Urban Heritage Tourism - Ginting, Nurlisa; Wahid, Julaihi (IPTEK Journal of Proceedings Series, 2017)
In supporting heritage tourism, emotional and psychological reactions between people and the places are required until the sites are no longer a mere identity of the geographical formation. The positive perception of people indicates satisfaction that is strongly influenced by the image of an urban area. The image defines the character of the place (spirit of place). In shaping the image of place, place identity takes a significant role and distinctiveness is one aspect of it that contributes in. This research aims to investigate the distinctiveness aspect and its influences in defining place identity of urban heritage area by using variable, i.e. landmark, uniqueness, particular character, and different perception. It focuses on the historical corridor of Medan City, Indonesia, chosen due to its significant role in the establishment of Medan City in past and the existence of historic buildings. This research combined qualitative and quantitative method through field observation and nine in-depth interviews as well as 360 questionnaires distribution, respectively to examine the perception of residents and visitors. This research contributes in defining place identity that can be used as evaluation and indicator for future planning. It will benefit in securing place identity towards support in urban heritage tourism that improves the quality of life. The result indicates that the existence of heritage buildings as landmark allows someone to have a unique affiliation to the research area. However, the diversity of interesting cultural activity, local product as well public facilities requires more improvement.